Relative speed fluctuations in discus throwing - Maheras, A. V. (Techniques Magazine, 2012)
The observation of the pattern of the discus speed relative to the system`s center of mass is a much better indicator of the propulsive or braking forces that the discus thrower is making on the discus than the observation of the absolute speed relative to the ground. Many practitioners believe that the main propulsive action of the discus should not commence until the left foot is planted in the ground in the front of the circle. In fact, practically all advanced throwers start the propulsive, "pulling" action much earlier than that. The danger here is that if throwers take such instruction literally and indeed wait until the left foot has landed in the front of the circle to start their final action, then the discus may advance forward enough along its path towards the front, without any force applied to it, and this could lead to a shortening of the effective final acceleration path of the discus. Such reduction will result in the reduction of the speed of the discus at release and eventually, the distance thrown.